Principles for developing academic writing skills in future German language teachers - Xushbokov , Oybek (The Lingua Spectrum, 2025)
This scientific article provides necessary information about strategies for developing academic writing skills for future German language teachers. The language skill of academic writing in German is one of the most very important productive language skills. The language skill of academic writing is closely related to free and creative types of writing. Writing skills can be acquired effectively and quickly only through the processes of writing a lot and practicing writing a lot. Writing skills are very important for our social relations and communication in our lives. The further develop communicative communication in the era of globalization. It is necessary to emphasize this important academic writing process within the teacher-student framework. If we look at history, it can be considered that the harmony of the art of calligraphy, which is one of our values, and the process of academic growth in our modern era is of great importance in the process of acquiring modern world knowledge and developing intercultural communication, which is reflected in the scientific article.